In silico drug repurposing for the identification of potential candidate molecules against arboviruses infection (2020)
Arboviral diseases caused by dengue (DENV), Zika (ZIKV) and chikungunya (CHIKV) viruses represent a major public health problem worldwide, especially in tropical areas where millions of infections occur every year. The aim of this research was to identify candidate molecules for the treatment of these diseases among the drugs currently available in the market, through in silico screening and subsequent in vitro evaluation with cell culture models of DENV and ZIKV infections. Numerous pharmaceutical compounds from antibiotics to chemotherapeutic agents presented high in silico binding affinity for the viral proteins, including ergotamine, antrafenine, natamycin, pranlukast, nilotinib, itraconazole, conivaptan and novobiocin. These five last compounds were tested in vitro, being pranlukast the one that exhibited the best antiviral activity. Further in vitro assays for this compound showed a significant inhibitory effect on DENV and ZIKV infection of human monocytic cells and human hepatocytes (Huh-7 cells) with potential abrogation of virus entry. Finally, intrinsic fluorescence analyses suggest that pranlukast may have some level of interaction with three viral proteins of DENV: envelope, capsid, and NS1. Due to its promising results, suitable accessibility in the market and reduced restrictions compared to other pharmaceuticals; the anti-asthmatic pranlukast is proposed as a drug candidate against DENV, ZIKV, and CHIKV, supporting further in vitro and in vivo assessment of the potential of this and other lead compounds that exhibited good affinity scores in silico as therapeutic agents or scaffolds for the development of new drugs against arboviral diseases. © 2019 Elsevier B.V.